Spatial Conflicts of Productive-Living-Ecological Land in Urumqi City of Xinjiang Wei Autonomous Region - Wang Shanshan; Wu Zhaopeng; Wang Juanjuan; Yin Huihui; Li Bincai (Shuitu baochi tongbao)
[Objective] Changes in productive-living-ecological land and its spatial conflicts in Urumqi City, Xinjiang Wei Autonomous Region, were studied in order to provide references for the optimal allocation of land resources in this region. [Methods] A spatial conflict measurement model at the grid scale was constructed for Urumqi City from the three factors of external pressure, vulnerability, and stability. The spatiotemporal characteristics of spatial conflicts in this region from 2000 to 2018 were then quantitatively evaluated. [Results] ① From 2000 to 2018, the northern part of Urumqi City was the main growth direction for urban living land, and the spatial pattern of agricultural production land showed a fragmentation trend. Ecological land was the main component of productive-living-ecological land in Urumqi City. Therefore, the occupation of new core ecological land by human activities should be avoided. ② The conflict levels of productive-living-ecological space in each period followed the order of stable and controllable > minor conflict > moderate conflict > heavy conflict. ③ The spatial unit of severe conflict had the largest increase, indicating that the scope of uncontrolled severe conflict in the study area was expanding, and should be the key area of spatial conflict regulation in Urumqi City. ④ There were some differences in spatial conflicts among different spatial types, and conflict intensity followed the order of productive space > living space > ecological space. [Conclusion] Changes in productive-living-ecological land in Urumqi City was strongly influenced by regional economic and social development. In the future, the phenomenon of conflict level gradually increasing due to the rapid expansion of living space should be gradually changed. The dynamic monitoring of urban living land should be given more attention, and the core ecological land should be protected in order to achieve more coordinated land use.